Use Various Mathematical Methods to Solve Three Dimensional Conduction Heat Equation in Cylindrical Coordinate - AHMED SALAR; Ahmed Jassim (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper we use the separation of variables method and L24c transform method to solve three-dimensional conduction heat equation in cylindrical coordinate and results plotted by using Matlab. It was concluded that L24c transform method is better than the method of separating the variables because it is a method that reaches the solution with fewer steps